2021
DOI: 10.18176/jiaci.0640
|View full text |Cite
|
Sign up to set email alerts
|

Validation of App and Phone Versions of the Control of Allergic Rhinitis and Asthma Test (CARAT)

Abstract: Supplementary material Supplementary Figure 1. Data collection timeline Supplementary Figure 2. Scatter plot showing the relationship between days between assessments and difference in Control of Allergic Rhinitis and Asthma Test total scores (CARAT-T).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…We included 16 original studies (published throughout 23 reports) in our systematic review (Table 1). 17–22,34–50 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included 16 original studies (published throughout 23 reports) in our systematic review (Table 1). 17–22,34–50 …”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarises the characteristics of included studies. The original Portuguese version of CARAT was used in 8 studies (11 reports) 17,19,34–39,42,46,47 . There were 2 studies (3 reports) on the Italian, 40,41,45 German and Dutch 18,21,40 versions of CARAT 22,43,44 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Technologies of information and communication, namely the telephone, offer a simple and effective alternative to paper-forms to keep monitoring these individuals ( 17 , 19 ). Evidence has shown that telephone administration of some health instruments for symptoms control ( 20 ) and measurement of HRQoL ( 21 , 22 ) is comparable to the in-person application. However, the psychometric properties of specific questionnaires to people with COPD still need to be explored; specifically, the reliability and validity of the telephone administration of the Functional Assessment of Chronic Illness-Fatigue-Subscale (FACIT-FS) and the St. George's Respiratory Questionnaire (SGRQ) have never been tested and only one study assessed these properties in the COPD Assessment Test (CAT) ( 23 ).…”
Section: Introductionmentioning
confidence: 99%